Revitalization Of Language Learning Management Through Mobile Learning - Safriyani Novitri; Sri Mulyani Rusli; Rahmatika Putri; Havid Ardi; Linda Sari Bulan; Novia Juita (INTERNATIONAL JOURNAL OF LANGUAGE PEDAGOGY, 2023)
The implementation of e-learning systems has resulted in new forms of pedagogical compulsion. The lack of planning stunned the lecturer, who may have taken impulsive moves to set up a range of media for their online sessions. This article explores the potential of digital technology to revitalize the Islamic University of Riau in English learning facilities and improve student learning outcomes. This study applies descriptive and qualitative research techniques to activate the opportunities contained in mobile applications for the benefit of learning English. Participants in this study were 25 ESP of second-semester law students at the Islamic University of Riau. Data were collected in two stages taking notes and a questionnaire to ascertain the extent of the study's outcomes and to explore Lecturer facilities and controls implemented in learning English through asynchronous learning with mobile learning. Findings show that reviving WhatsApp by offering student-planned activities improves students' English proficiency. The result was to create activities that encourage students to take a positive role and encourage their courage to speak English because the WhatsApp application can support activities and prepare students to take an active role.